The Double-Edged Sword of Third-Party Resources: Examining Use and Financial Burden of Extracurricular Tools in Medical Students [version 2; peer review: 1 approved, 2 approved with reservations] - Dimitrios Papanagnou; Saaniya Farhan; Andres Fernandez; Meryem Guler; Drake Kienzle; Faizaan Siddique (MedEdPublish)
Background According to the Association of American Medical Colleges (AAMC) Year 2 questionnaire, the percentage of students using online medical education videos (Boards and Beyond®Sketchy Medical®, Youtube) at least once per week increased from 47.7% (2015) to 70.1% (2022). Transition to virtual learning in 2020 fostered a greater reliance on these online third-party resources (i.e., educational tools distinct from formal medical curriculum), yet existing literature have rarely evaluated their efficacy. As students in this landscape, we aimed to review the usage, efficacy, and drawbacks of third-party resources and their financial burden on students. Methods Four authors searched PubMed from June-July 2023 using the search terms “prevalence,” “efficacy,” and “disparities introduced by third-party board preparation resources.” All peer-reviewed articles in English were evaluated. No inclusion or exclusion criteria were implemented. References were mined for additional results, per the discretion of each reviewer. Results 31 studies were examined for common themes and findings to provide a snapshot of the existing literature. Studies suggest third-party resources are used in a task-dependent manner with a supplemental role to lectures during the preclinical years and a primary role for United States Medical Licensing Examination (USMLE) preparation during clinical years. Medical students access these resources to perform well on board exams, prompted by studies demonstrating their efficacy in increasing USMLE Step 1 scores. Though certain resources have been frequently cited for improving board performance (e.g., First Aid, UWorld), students combine multiple third-party resources to best serve their preparation. Subscription-pricing of most third-party resources and 12-month access prices range from $100 to $479. Conclusion Third-party resource use may contribute to an increased financial strain on students. This, coupled with overwhelming medical student debt, may exacerbate socioeconomic disparities in medical education. Institutions should evaluate third-party resource use among students and consider provisions to increase access to them.